Complicit masculinity of judges - Eylem Ümit Atılgan (Oñati Socio-Legal Series)
The paper focuses on how unjust provocation reduction, regulated in Article 29 of the Turkish Penal Code, is applied in cases of violence against women, LGBTI, and transgender individuals in Turkey, also known as "masculinity sentence reduction" by feminist lawyers. In particular, I will look into case files in which the "masculinity defence" made by almost all perpetrators in femicide cases is accepted by the court as a justification for reducing the sentence of the perpetrator. I will examine how masculinity is portrayed in judicial decisions, specifically looking at provocation defences to demonstrate how jurisdiction plays a part in perpetuating masculine domination within society. Using theories of masculinity and masculine domination, I will try to reveal the contribution of judges to the "masculine legal culture" as a form of "complicit masculinity".